Exploring the Experiences of Undergraduate Medical Students with Online Open-Book Exams: An Exploratory Qualitative Study - Khaulah Jawed, Tahira Sadiq, Azhar Rashid, Rehan Ahmed Khan, Raheela Yasmin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During COVID-19 medical education system in our ever-burgeoning societies thus saw a paradigm shift from in-person interactions to a virtual ones. In Pakistan, HEC also preferred online open-book exams (OBE) to closed-book exams (CBE) as an assessment strategy; issued guidelines accordingly. The absorption of this new assessment strategy proved daunting for undergraduate (UG) medical students. Careful understanding of their experiences proffers a seamless integration of online OBE in online assessment as a whole. Methods: The Qualitative exploratory design has been utilized. The sampling technique includes purposeful sampling with maximum variation in sampling type. The sample size was eighteen students for three FGDs (six students in each group). Online FGDs were conducted and thematic analysis was done with verbatim transcription of data. Result: Eight themes have been extracted from the data. The themes include understanding of students with online OBE, practice and training for online OBE, preparation for students for OBE, attempting online OBE, the spectrum of emotions, educational impact and benefits of online OBE, difficulties encountered during online OBE, and anticipated future of OBE in medical education. Conclusion: Experiences of UG medical students in online OBE indicate its potential in future applications, such as formative assessment, teaching strategy, complementing conventional exams, and assessing real-life workplace situations. Relevant findings have enabled the furnishing of one model for the effective utilization of online OBE for institutions and students.